Experimental and analytical studies on 2D precast concrete sub-structure with and without post-tensioned tendon under column removal scenario - Weng, Huan Ting (Nanyang Technological University, 2022)
Progressive collapse has been one of the most devastating types of structural collapse, and it had caused numerous casualties and financial strains on the countries. Ever since the progressive collapse of Ronan Point apartment in 1968, extensive research had been carried out to mitigate the probability of progressive collapse. This report presents a comprehensive experimental and analytical investigation of precast concrete sub-structure with and without post-tensioned tendon under column removal scenario. The experimental study was performed on three one-quartered scaled beam-column precast sub-structures with different post-tensioned conditions to study load-resisting mechanisms in resisting progressive collapse subjected to middle column removal scenario. The report presents the test results, which include the load-displacement curve, ultimate load capacity, crack patterns and failure modes of all three specimens. From the test results, it can be concluded that precast concrete specimen with bonded post-tensioning achieved the highest ultimate capacity , while unbonded post-tensioning presented a highly ductile behaviour of the structure in resisting progressive collapse under middle column removal scenario. In addition, a simplified analytical model and worked examples have been proposed in the report to retrofit a quick tool in design beam-column sub-structures against progressive collapse.